Inventory and Monitoring of Land Degradation Processes Using Space Data - Christian, Binal A; Dhinwa, P S; Ajai, Ajai (Annals of Arid Zone, 2019)
Land degradation is one of the major environmental hazards, affecting theliving conditions of millions of people all across the world. Inventory and monitoringof the land degradation status are the primary requirement in preparation of mitigationplan to combat land degradation. The present paper, therefore, aims at the creationof spatial inventory of land degradation processes using satellite data. Multi-seasonLandsat TM data of 30 m spatial resolution, pertaining to the years 1992, 2001 and2016, have been analysed to prepare land degradation maps of Ballia district, UttarPradesh state in northern India. Monitoring and assessment of the desertification hasbeen carried out for a period of 24 years. In this study, an attempt is made to monitorthe changes in land degradation status during 1992 to 2016 by using multi-temporalsatellite data. Water logging and sodicity in agricultural land are the major processesof land degradation active in Ballia district. Analysis of satellite data reveals that areaunder sodicity in agriculture land has increased from 23.04 km2 in 1992 to 25.08 km2in 2016, while water logging in agricultural land has increased from 199.92 km2 in 1992to 210.25 km2 in 2016.Key words: Land degradation, monitoring, multi-temporal, satellite data